Lost in a book - Donnelly, Jennifer (Beauty and the Beast (Disney Press), 2017)
When Belle comes across a mysterious book in the beast's library, she finds herself transported to a fantasy world of her dreams, and she must uncover the secrets about the book before she is lost inside forever.